Geotechnical engineering educational modules demonstrating measurement and regulation of soil moisture - Garg, Ankit; Huang, Yuanxu; He, Huang; Huang, Xilong; Lin, Peng; Kalra, Kanishk; Mei, Guoxiong; Khandare, Vaibhav; Singh, Lovepreet (Computer applications in engineering education, 2022)
With the rapidly changing needs of the construction industry and higher education, Conceive—Design—Implement—Operate (CDIO) educational framework is essential in delivering basics and practical aspects to undergraduate students. This study presents an attempt to explore the use of hardware and software applications for geotechnical engineering education. An example for development of hardware (Arduino UNO) and software applications (Mobile applications) for estimating soil moisture and its regulation is presented. The study provides a new learning environment, where students from civil engineering (major) can work hand to hand with that from electronics (minor) to develop applications for soil moisture measurement. A collaborative workshop is proposed and executed. The workshop includes basic concepts related to hardware (Time domain reflectometry [TDR] probe, Arduino UNO, and Water flow measurement) and software (LabVIEW and Android studio programming platforms) followed by project implementation in a group of 5–6 students. Satisfaction and comprehension were found to increase significantly for subjects (electronics and optics) to students of civil engineering background. The adopted tools represent economical means for application in conventional classrooms as well as laboratories for undergraduate students with a civil engineering background. This integration of the digital and physical world is an attempt at approaching soil mechanics mathematics from technology and arts from a scientific perspective. The examples presented in this study can be useful for developing open‐source laboratories within the framework of the undergraduate curriculum in civil engineering.